2009
DOI: 10.1016/j.jacc.2009.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Aneurysms After Drug-Eluting Stent Implantation

Abstract: After DES implantation, CANs are rare and may be detected in asymptomatic patients. However, CANs are frequently associated with adverse clinical events as a result of DES restenosis and DES thrombosis. Further studies are required to determine the implications of this distinct new entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(40 citation statements)
references
References 34 publications
3
36
1
Order By: Relevance
“…Our findings are also corroborated by a recent cohort study in patients who had undergone DES implantation. During a mean follow-up period of 399 days, Alfonso et al (27) reported a coronary artery aneurysm rate of 1.3% after DES implantation. In 4 of 15 patients with a documented aneurysm, the aneurysm was found at the zone of stent overlap, which suggests excessive vessel remodeling as a result of the high density of drug or polymer.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also corroborated by a recent cohort study in patients who had undergone DES implantation. During a mean follow-up period of 399 days, Alfonso et al (27) reported a coronary artery aneurysm rate of 1.3% after DES implantation. In 4 of 15 patients with a documented aneurysm, the aneurysm was found at the zone of stent overlap, which suggests excessive vessel remodeling as a result of the high density of drug or polymer.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of CAAs ranges from 0.3 to 5.3%; a pooled analysis states a mean incidence of 1.65% (18). The incidence of giant CAAs is as low as 0.02%, while the incidence of those associated with congenital artery fistulae are 5.9% (3).…”
Section: Epidemiologymentioning
confidence: 99%
“…1 Hypersensitivity vasculitis has been noted with first generation DES [1][2][3] ; however, it has rarely been described after EES implantation 4 and, to our knowledge, never within 3 weeks of implantation. As such, this would be the earliest report of aneurysm formation after EES implantation.…”
mentioning
confidence: 99%
“…There were 90% in-stent restenoses proximal and distal to the aneurysm (Figure [D]). The D1 and OM1 remained occluded.Although the polymers used for drug-delivery in drug-eluting stents (DES) are highly biocompatible, they can rarely incite a severe inflammatory reaction consisting of eosinophils and lymphocytes involving all 3 arterial layers, leading to aneurysm formation and significantly increasing the risk of stent thrombosis.1 Hypersensitivity vasculitis has been noted with first generation DES [1][2][3] ; however, it has rarely been described after EES implantation 4 and, to our knowledge, never within 3 weeks of implantation. As such, this would be the earliest report of aneurysm formation after EES implantation.…”
mentioning
confidence: 99%